An empire on display : English, Indian, and Australian exhibitions from the Crystal Palace to the Great War - Hoffenberg, Peter H., 1960- (University of California Press, 2001)
The exhibitions of the Victorian and Edwardian eras are the lens through which this book examines the economic, cultural, and social forces that helped define Britain and the Empire. It focuses on exhibitions in England, Australia, and India from the Great Exhibition to the Festival of Empire.